Images of Dead Poets in Roman Elegiac and Lyric Underworld - Vasconcellos, Paulo Sérgio de (Classica - Revista Brasileira de Estudos Clássicos, 2017)
In this paper I analyse and compare the representations (or self-representations) of poets in the underworld in elegiac and lyric Roman poetry. I focus especially on five poems: Tibullus I.3; Propertius II. 34; Ovid, Amores II.6 (birds as poets) and III.9; Horace, Odes II.13. It is not my intention to give a detailed interpretation of the whole poems; my principal aim is to analyse how dead poets are pictured in two different genres, the elegiac and the lyric, which share certain features (for instance, we can have in some lyric poems the poetic persona of a lover, the amator, which characterizes erotic elegy discourse, and some similar topics, as the metaphor of love as illness, etc.). At the end of this paper, I will point to the images of dead poets that are (I think) the most representative of the difference between elegiac and lyric genres. In the footnotes I provide some bibliographical references on studies and commentaries about each of the poems I treat here.